Economic factors of increasing fertility in the Volga Federal District: a retrospective analysis (2000–2020) - Ch. I. Ildarhanova; G. N. Ershova; Yu. N. Ershova; A. A. Ibragimova (Модернизация, инновация, развитие, 2022)
Purpose: to determine the economic factors that steadily influenced reproductive trends in the Volga Federal District in 2000-2020, their regional differentiation. The hypothesis of the study: the dynamics of the birth rate is predetermined, among other things, by economic factors (of a general economic nature and economic activity of households). With a positive change in the economic well-being of the population and households, stable prerequisites are formed for the growth of the birth rate in the Volga Federal District.Methods: the correlation and regression analysis of the total fertility rate and economic predictors for 2000-2020 of the Volga Federal District regions was used. Econometric prerequisites for determining reproductive trends are formed based on changes in macro- and microeconomic indicators of the economic well-being of the region and individual households.Results: regional differences in the influence of economic factors on fertility are revealed: direct linear dependence on the volume of investments per capita and the level of employment; inverse dependence on the level of poverty and the share of household spending on food (except for the Republic of Bashkortostan). When assessing the inverse linear dependence on the indexation of prices for primary housing, the coefficient of determination is insufficient (except for the Udmurt Republic), as in the case of assessing the impact of the unemployment rate (the factor is insignificant for the Republic of Bashkortostan, Kirov Region, Perm Krai). The growth and decrease in monthly consumer spending lead to a decrease in the birth rate.Conclusions and Relevance: one-factor regression analysis showed that in the Volga Federal District, the formation of reproductive trends is negatively affected by an increase in the share of spending on essential goods. Multivariate regression analysis revealed a correlation of fertility rates with a steady increase in the level of employment. The presented approach can be used to describe the prerequisites for the formation of stable reproductive trends in other districts and regions of Russia for the implementation of preventive measures of the demographic policy of the state in order to maintain the stability and positive development of the demographic situation, prognostic estimates of trends of deviation from the positive trend.